2008
DOI: 10.1029/2007pa001539
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal‐decadal climate variability from multicoral oxygen isotope records in the South Pacific Convergence Zone region since 1650 A.D.

Abstract: In the South Pacific, interdecadal‐decadal oceanic and atmospheric variability, referred to as the Interdecadal Pacific Oscillation (IPO), is most pronounced in the South Pacific Convergence Zone (SPCZ) salinity front region. Here we have used annual average oxygen isotope (δ18O) time series from five coral cores collected from Fiji and Tonga in this region to construct a Fiji‐Tonga Interdecadal‐Decadal Pacific Oscillation (F‐T IDPO) index of low‐frequency (>9 and <55 years) climate variability back to 1650 A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 70 publications
1
104
0
Order By: Relevance
“…In this study, we do not consider records derived from multiple-year sampling intervals (Linsley et al, 2006(Linsley et al, , 2008 nor bulk averages (Hendy et al, 2002;Calvo et al, 2007), which are straightforward extensions of our model. Thus, for error-free annually banded proxies, i = = 1 year exactly (Fig.…”
Section: Univariate Model Formulationmentioning
confidence: 99%
“…In this study, we do not consider records derived from multiple-year sampling intervals (Linsley et al, 2006(Linsley et al, , 2008 nor bulk averages (Hendy et al, 2002;Calvo et al, 2007), which are straightforward extensions of our model. Thus, for error-free annually banded proxies, i = = 1 year exactly (Fig.…”
Section: Univariate Model Formulationmentioning
confidence: 99%
“…Nevertheless, relative to the large quantity of high-resolution studies, annual to multi-year resolution coral-based studies are still relatively rare. In addition, of those coral-based studies undertaken at annual to pent-annual resolutions (Dunbar et al 1994;Cole et al 2000;Hendy et al 2002;Pelejero et al 2005;Calvo et al 2007;Linsley et al 2008;Abram et al 2009;Wei et al 2009;Deng et al 2013;Zinke et al 2014), few have focused on the replication of the lowresolution geochemical records of multiple coral cores. Some studies have evaluated the climatic significance of annual coral records averaged using monthly or sub-annual values from each year (Lough 2004;Smith et al 2006;Pfeiffer et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The natural variability in P/Ca records among colonies and taxa must be assessed carefully to determine the degree of reproducibility possible for reliable PO 4 SW reconstructions. Recent work on previously established hermatypic coral proxies (d 18 O, Sr/Ca, and Cd/Ca) has shown that averaged multicolony records can yield more accurate reconstructions of climate (DeLong et al, 2007;Goodkin et al, 2007;Linsley et al, 2008;Matthews et al, 2008).…”
Section: Introductionmentioning
confidence: 99%